The Influence of the Ease of Use of the JMO Application on the Satisfaction and Loyalty of BPJS Ketenagakerjaan Participants - Mikha Zefanya Nainggolan Nainggolan; Helda Tarigan; Eca Nehemia Bregin Hutagaol; Agrien Yolanda Romagina Malau; Habieb Pahlevi; Asma Khalid; Yushita Marini (Journal of Digital Scholarship in Archives and Information, 2025)
Background of study: The digital transformation of public services in Indonesia has prompted institutions like BPJS Ketenagakerjaan to adopt technology-based platforms to enhance accessibility and efficiency. One such initiative is the Jamsostek Mobile (JMO) application, designed to provide participants with self-service access to essential features such as checking balances and submitting claims. The perceived ease of use of such platforms plays a critical role in determining user satisfaction and long-term engagement. Aims and scope of paper: This paper aims to analyze the influence of the perceived ease of use of the JMO application on user satisfaction and loyalty among BPJS Ketenagakerjaan participants. The scope of the study is conceptual, focusing on the theoretical relationships between ease of use, satisfaction, and loyalty within the context of digital public services. Methods: This study employs a conceptual literature review method based on the Technology Acceptance Model (TAM). Data were sourced from peer-reviewed journals, reports, and previous research published between 2021 and 2025, using keywords such as “ease of use,” “user satisfaction,” “loyalty,” and “digital public services.” Result: The findings indicate that intuitive design, clear navigation, and accessible features significantly influence user satisfaction. In turn, satisfaction strongly contributes to user loyalty. However, external factors such as digital literacy, service responsiveness, and internet infrastructure also moderate these relationships. Conclusion: To ensure the sustainability of the JMO application, BPJS Ketenagakerjaan must continuously improve usability, technical infrastructure, and user support systems. Enhancing ease of use is essential not only for increasing satisfaction but also for fostering long-term user loyalty in digital public services.